Mechatronics by Bond Graphs An Object-Oriented Approach to Modelling and Simulation - Damic, Vjekoslav; Montgomery, John (Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book presents a computer-aided approach to the design of mechatronic systems. Its subject is an integrated modeling and simulation in a visual computer environment. Since the first edition, the simulation software changed enormously, became more user-friendly and easier to use. Therefore, a second edition became necessary taking these improvements into account. The modeling is based on system top-down and bottom-up approach. The mathematical models are generated in a form of differential-algebraic equations and solved using numerical and symbolic algebra methods. The integrated approach developed is applied to mechanical, electrical and control systems, multibody dynamics, and continuous systems. .